Prostate-specific membrane antigen as a target for prostate cancer PET imaging - Malaspina, Simona (fi=Turun yliopisto|en=University of Turku|, 2023)
Prostate-specific membrane antigen (PSMA) is a transmembrane protein overexpressed in prostate cancer (PCa) cells. In the last decade, PSMA-targeting positron emission tomography (PET) has gained increasing acceptance for PCa imaging. Among the different available PSMA ligands, theranostic agents that can be labelled with both diagnostic and therapeutic radioisotopes have raised particular interest. Androgen deprivation therapy (ADT) is known to upregulate PSMA expression. However, studies investigating this phenomenon in humans are limited. In the clinical context, while the use of PSMA PET has been established in detecting recurrence after radical treatment, the role of PSMA PET in primary staging was only recently affirmed. The aim of this doctoral thesis was to investigate novel aspects of PSMA PET imaging, from the kinetics of a novel theranostic radiotracer, through the physiology of PSMA expression, to its use for primary staging in the clinical practice. The uptake kinetics of radiohybrid [18F]-rhPSMA-7.3 in PCa lesions and reference tissues were assessed in a prospective Phase I trial and demonstrated dominant irreversible components. The uptake in PCa lesions and lesion-to-reference ratios increased over time, with the optimal visual detection starting from 60 minutes postinjection. Two prospective studies demonstrated a heterogeneous increase in PSMA uptake after short-term ADT (PSMA flare) in treatment-näive PCa patient, most evidently seen in bone metastases. This phenomenon was negatively correlated with glucose metabolism, which suggests that lesions with low or absent flare might be more aggressive. Finally, [ 18F]-PSMA-1007 PET/computed tomography (CT) was prospectively compared to whole body magnetic resonance imaging (WBMRI) and CT in the primary nodal staging of patients with unfavourable intermediate or highrisk PCa. The study demonstrated improved sensitivity and accuracy while maintaining high specificity.

Prostataspesifinen membraaniantigeeni eturauhassyövän PET-kuvantamisessa Prostataspesifisen membraaniantigeenin (PSMA) ilmentyminen on voimakkaasti lisääntynyt eturauhassyövän solukalvoilla. Tämän takia PSMA on erinomainen kohde eturauhassyövän positroniemissiotomografia(PET)-kuvaukselle. PSMA PET:n käyttö eturauhassyövän kuvantamisessa on lisääntynyt selvästi viime vuosikymmenen aikana ja PSMA:han sitoutuvia merkkiaineita on kehitetty useita. Erityistä kiinnostusta ovat herättäneet ns. teranostiset merkkiaineet, jossa sama PSMA-ligandi voidaan leimata sekä PET-kuvantamiseen että kehonsisäiseen sädehoitoon tarkoitetuilla isotoopeilla. Androgeenideprivaatioterapia (ADT) tiedetään lisäävän PSMA:n ilmenemistä, mutta tätä ilmiötä on tutkittu hyvin niukasti. Yleisin, kliinisesti vahvistettu PSMA-PET:n käyttöindikaatio on eturauhassyövän hoidon jälkeisen taudin uusiutumisen havaitseminen, mutta myös PSMA-PET:n rooli taudin levinneisyyden selvittämisessä on tarkentumassa. Tämän väitöskirjan tarkoituksena oli tutkia PSMA-PET-kuvauksen uusia näkökohtia, kuten uuden teranostisen merkkiaineen kinetiikkaa, hormonihoidon vaikutusta PSMA-PET:n löydöksiin sekä PSMA-PET:n suorituskyky eturauhassyövän levinneisyyden selvittämisessä. [ 18F]-rhPSMA-7.3:n kinettisen analyysin tulokset osoittivat, että tautipesäkkeiden aktiivisuudet sekä pesäke/vertailukudos-aktiivisuussuhteet voimistuivat ajan myötä ja optimaalinen pesäkkeiden visuaalinen paikallistaminen alkoi 60 minuuttia injektiosta. Kahdessa muussa tutkimuksessa osoitettiin, että PSMA:n ilmentymisen lisääntyminen lyhytaikaisen ADT:n jälkeen (PSMA-flare) on heterogeenista ja voimakkainta luustoetäpesäkkeissä levinnyttä eturauhassyöpää sairastuvilla potilailla. PSMA-flare-ilmiö korreloi negatiivisesti glukoosin aineenvaihduntaan, mikä viittaa siihen, että matala PSMA-flare tai sen puuttuminen on yhteydessä etäpesäkkeiden aggressiivisuuteen. Lisäksi [ 18F]-PSMA1007 PET/tietokonetomografia (TT) verrattiin koko kehon magneettiin ja TT:hen korkean riskin eturauhassyöpäpotilailla. Tutkimus osoitti PSMA-PET/TT:n korkeamman herkkyyden ja tarkkuuden.